Effects of the EEC's Variable Import Levies - Sampson, Gary P.; Snape, Richard H. (Journal of Political Economy, 1980)
The mechanics of variable import levies, as used by the EEC for agricultural products, are analyzed. Attention is paid to their destabilizing effects on world markets and to the way in which they can capture not only economic rent associated with trade restrictions but also the subsidy payments of exporting countries. Statistics are provided showing the importance of variable levies in the EEC, their ad valorem incidence, and variation, and a rough estimate is made of their depressing effect on world prices.